Small Bowel Adenocarcinomas Complicating Crohn's Disease Are Associated With Dysplasia: A Pathological and Molecular Study. Issue 9 (15th July 2014) - Svrcek, Magali; Piton, Gael; Cosnes, Jacques; Beaugerie, Laurent; Vermeire, Severine; Geboes, Karel; Lemoine, Antoinette; Cervera, Pascale; El-Murr, Nizar; Dumont, Sylvie; Scriva, Aurélie; Lascols, Olivier; et al.
Abstract : Background: Crohn's disease (CD) is associated with an increased risk of small bowel adenocarcinoma (SBA). However, there are no guidelines for the screening and early diagnosis of SBA. Colorectal cancer associated with chronic colitis arises from dysplasia. High-risk patients benefit from surveillance colonoscopies aimed to detect dysplasia. The dysplasia–carcinoma sequence remains poorly documented in CD-associated SBA. Moreover, molecular data about SBA complicating CD and associated dysplasia are very limited. We therefore assessed dysplasia and several key molecular markers of carcinogenesis in SBA and dysplasia developed in patients with CD. Methods: Forty-five SBA complicating CD and 4 specimens with dysplasia without SBA were screened. In SBA, we looked for dysplasia and determined their pathological characteristics (type, grade, distribution). We also stained for mismatch repair proteins (MLH1, MSH2, MSH6, PMS2), p53, β-catenin, and p16 and looked for KRAS, BRAF and PIK3CA mutations. Results: All neoplastic lesions, except 1 lesion, were found in inflamed mucosal areas. Dysplasia was found in 20 of 41 patients with SBA (49%). Dysplasia was flat or raised, low grade or high grade, and adjacent or distant to concomitant SBA. Molecular markers of SBA carcinogenesis complicating CD were similar to those observed in chronic colitis-related colorectal cancer ( KRAS, BRAF, p53, MSI), although differences were observed for β-catenin and p16. No PIK3CA mutations were observed. Conclusions: These results suggest that there is an inflammation–dysplasia–adenocarcinoma sequence in at least half of CD-related SBA, similar to what is observed in chronic colitis-related colorectal cancer and may have implications for the prevention and treatment of this cancer.